Psychological Stress and the Human Immune System A Meta-Analytic Study of 30 Years of Inquiry. Articles]. - Segerstrom, Suzanne C.
The present report meta-analyzes more than 300 empirical articles describing a relationship between psychological stress and parameters of the immune system in human participants. Acute stressors (lasting minutes) were associated with potentially adaptive upregulation of some parameters of natural immunity and down regulation of some functions of specific immunity. Brief naturalistic stressors (such as exams) tended to suppress cellular immunity while preserving humoral immunity . Chronic stressors were associated with suppression of both cellular and humoral measures. Effect of the events sequences varied according to kind of event (trauma vs loss) Subjective reports of stress generally did not associate with immune change. In some cases , physical vulnerability as a function of age or disease also increased vulnerability to immune change during stressors-- (from the author